Voices Unveiled: Social Media's Role in Empowering Indonesian Muslim Women Politicians - Ismandianto, Ismandianto; Sazali, Hasan; Rubani, Mardiah; Muchid, Muchid; Muhammadi, Qasem (UIN Sunan Gunung Djati Bandung, 2023)
This study investigates the role and strategies of Muslim women politicians in utilising social media during local head elections in post-conflict regions in Indonesia. By employing a mixed-methods approach integrating both qualitative and quantitative data, this research analysed 371 comments from Twitter that were captured using the Netlytic platform, a cloud-based tool that assesses social media dynamics. The findings reveal that social media platforms significantly amplify the political voice and influence of Muslim women, providing them with a vital tool for overcoming traditional barriers in political communication. The study contributes to the broader understanding of digital communication in political campaigns, particularly highlighting how gender and cultural dynamics influence political participation in Muslim-majority regions. It also suggests strategic directions for future campaigns to enhance the visibility and effectiveness of women politicians.